“Отнесение к ценности”, смысл и социальное изменение - Бурлачук, В. (Социология: теория, методы, маркетинг, 2001)
Sense is discussed within the ‘understanding sociology’ tradition. Criticizing the phenomenological approach to social sense, the author supposes that a source of subject’s sense orientations is situated in the inter-subjective world, and this idea makes it possible to determine sense as objective and existing out of individual’s consciousness. The ‘anonymous intentionality’ problem raises a question of existing ‘objective senses’, ideal objectivities taking part in sense development of the social world.